2015
DOI: 10.7455/ijfs/4.1.2015.a10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of cassava starch films as affected by different plasticizers and different relative humidity conditions

Abstract: The influence of plasticizer type (glycerol and sorbitol), its content (starch:plasticizer ratio of 1:0.15; 1:0.20; 1:0.25 and 1:0.30) and the relative humidity conditions (43, 58, 75 and 85%) on the mechanical properties of cassava starch films was studied. Both plasticizers seemed to integrate homogeneously in the film matrix. The incorporation of different concentrations of plasticizers affected the mechanical properties of the cassava starch films. Plasticizer ratio directly influenced the force values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 35 publications
1
3
0
2
Order By: Relevance
“…Results showed that thickness of biopolymeric films was increased by increasing the concentration of glycerol, and it can be due to the fact that when plasticizer was added in the concentrated solution, a large amount of dry matter (starch+protein) leads to increase in thickness of films [69,70]. Similar finding was reported by Lagos et al that the increased thickness of biopolymeric films was observed when there was an incorporation of glycerol [71].…”
Section: Standardization Of Plasticizer (Glycerol)supporting
confidence: 80%
“…Results showed that thickness of biopolymeric films was increased by increasing the concentration of glycerol, and it can be due to the fact that when plasticizer was added in the concentrated solution, a large amount of dry matter (starch+protein) leads to increase in thickness of films [69,70]. Similar finding was reported by Lagos et al that the increased thickness of biopolymeric films was observed when there was an incorporation of glycerol [71].…”
Section: Standardization Of Plasticizer (Glycerol)supporting
confidence: 80%
“…It is known that water is an effective plasticizer for starchbased EFs. The water molecule is positioned between the polymeric matrix components, diminishing the hydrogenbonding interactions and decreasing the film's strength and rigidity (Bonilla-Lagos et al, 2015). For this reason, at low storage RH, intermolecular interactions between starch and plasticizers could remain stable without significantly affecting the EFs' mechanical properties.…”
Section: Puncture Resistance (Pr)mentioning
confidence: 99%
“…Berbagai riset dan pengujian yang ada diantaranya, pengujian campuran yang berbeda bio plastic dari protein dan pati albumen (kentang dan jagung) telah digunakan sebagai bahan mentah untuk bioplastik dengan transparansi tinggi dan sifat mekanis yang sesuai [7]. Penggunaan plastisizer glycerol dan sorbitol dan pengaruh penambahan bahan tersebut pada pembuatan plastic dari bahan cassava starch (pati singkong) [8]. Penggunaan cassava starch juga diungkapkan pada penelitian biodegradable dan non-retrobiodegradable dari [9].…”
Section: Latar Belakang Masalahunclassified